Social Determinants of Health and Effects on Cardiovascular Disease - Amireh, Karim; Makaryus, Amgad N. (International Journal of Angiology, 2025)
Research has shown that social determinants of health (SDOH) can influence health outcomes by up to 30 to 55% and can account for 80 to 90% of a person's health status. Our review evaluates SDOH in cardiovascular disease patients and assesses their impact in the field of cardiology as evidenced by research in the literature. Such SDOH as housing availability, access to healthy foods, access to transportation, access to medications, quality of living conditions, quality of schooling, and many other factors, have a great impact upon our patients' outcomes. Nowhere is this more true than in the field of cardiovascular disease, which is the leading cause of death worldwide. By recognizing SDOH and managing them through detection and prevention, patient outcomes can be affected in a positive direction. The key to being successful in this endeavor is to improve our patients' health literacy, promote prevention, and ameliorate the negative factors that affect health outcomes.
Keywords: social determinants of health; cardiovascular disease; cardiology; socioeconomic; health care access; economic status; community